(untitled) (The Pakistan Development Review, 2001)
For the new round of WTO multilateral trade liberalisation negotiations to be successful, the world will need to be more enthusiastic and flexible about opening markets. Partisans will need to submerge their self-interests, and the U.S. will need to take the initiative for more open markets. This paper makes the case that only modest changes in the U.S. domestic grain, oilseed, and cotton programmes are needed for compatibility with global free trade. The Federal Agricultural Improvement and Reform (FAIR) Act of 1996 and related policy changes in the 1990s brought fundamental reforms compatible with freer domestic and foreign markets. Chief among these were a shift from coupled deficiency payments to decoupled direct payments, an end to supply management, and less engagement of government in commodity stock accumulation and export subsidies. Converting commodity price support to recourse loans while ending all but administrative cost subsidies to crop insurance would go far to liberalise grain, oilseed, and cotton policies. Unilateral termination of commodity programmes including direct payments totalling 42 percent of net cash farm income in year 2000 would appear to be traumatic to producers. However, reduction of direct payments could be offset (for farm income) by rising farm commodity prices and receipts resulting from (1) less farm output attending lower loan rates and crop insurance subsidies, and (2) world farm commodity price-enhancement from freer global trade.